Alienation: The critique that refuses to disappear. (October 2015) - Kalekin-Fishman, Devorah; Langman, Lauren
Although it is often condemned as an imprecise concept, alienation continues to flourish as critique in contemporary philosophy, theology, and psychology, as well as in sociology. Historically originating in Roman law, where it referred to the transfer of land ownership, alienation has since been applied extensively to analyses of labor relations, politics, and culture. In the 19th century, Marx showed that workers' alienation, their dehumanization and estrangement, was a consequence of the structure of exploitation in capitalist industry. The concern was echoed in Weber's metaphor of the 'iron cage' as an outcome of rationalized structures, as well as in Durkheim's conceptualization of anomie as a variant of alienation causing socially induced psychological states. Today, while research in the structural tradition does not assume that people necessarily are aware of their condition, researchers who assume that alienation is a conscious experience have invented scales to measure its intensity. Continuing both the structural and the psychosocial traditions, researchers now study alienation in relation to uses of digital technologies and new forms of exploitation in work, as well as in politics and popular culture. Alienation is also studied in families, especially in investigations of parenthood.